KAJIAN HUKUM KEWENANGAN PENYELIDIKAN ANTARA KEPOLISIAN, KPK DALAM PEMBERANTASAN PIDANA KORUPSI DARI KELEMBAGAAN NEGARA - Sumiaty Adelina Hutabarat (Jurnal Spektrum Hukum PMIH UNTAG Semarang, 2020)
There are two law enforcement agencies combating corruption, namely the Corruption Eradication Commission (KPK) and the Police, having the same authority, but in implementing authority there are differences, for example in the application of laws that govern the two institutions.The problem that becomes the study of this research is how the problem of the existence of the KPK as an institution to eradicate corruption has the authority regulated in RI Law No. 30 of 2002 concerning the Corruption Eradication Commission, whose authority lies with the Police regulated in RI Law No. 2 of 2002 concerning the National Police of the Republic of Indonesia which refers to the Criminal Code The results of the study showed that the resolution of the dispute between the Police and the Corruption Eradication Commission in the investigation of corruption was carried out by coordinating the Corruption Eradication Commission and the Police in Corruption Criminal Investigations. Law number 30 of 2002 concerning the Corruption Eradication Commission regulates the relationship between the performance of the KPK and the Police regarding investigations, investigations and prosecutions.Settlement of authority disputes between the Police and the KPK should be the authority of the Supreme Court, due to judicial review under the Supreme Court Law. The right to test the law is the application of a balanced and balanced government. The Corruption Eradication Commission was formed by the Law 30/2002 whereas the Indonesian Police was formed by the 1945 Constitution, article 30 paragraph 4.Keywords : Authority, investigation, KPK